PENGARUH KESADARAN MEMBAYAR PAJAK, PEMAHAMAN TENTANG PAJAK, SANKSI PAJAK DAN KUALITAS PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Pada Kantor Pelayanan Pajak Pratama Tampan Pekanbaru) - Adinata, Amelya; Taufik, Taufeni; -, Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is to investigate the influence of the tax paying consciousness, understanding of taxes, tax penalties and quality of service tax on tax compliance. The population in this study is the individual taxpayer. The sample in this study is 100 respondents who have met the criteria of the sample. The results of this research showt that awareness of paying taxes significantly affect tax compliance, with 2.669 t-test, t-table 1.985 and 0.009 significant value. An understanding of significant tax effect on tax compliance, with 2,793 t count, the t-table 1.985 and 0.006 significant value. Sanctions taxes significantly affect tax compliance, with 2.363 t-test, t-table 1.985 and significant value of 0.020. The quality of tax services significantly affect tax compliance, with 2.872 t-test, t-table 1.985 and 0.005 significant value. The value of Adjusted R Square of 0.498. This means that 51.8% variable taxpayer compliance can be explained by the consciousness of paying taxes, an understanding of taxes, tax penalties, the tax service quality. While the remaining 48.2% is explained by other variables outside of this researchKeywords: consciousness, tax, penalties, quality, and compliance.